Climate Change Impacts on the Water Resources in the Danube River Basin and Possibilities to Adapt: – The Way to an Adaptation Strategy and its Update - Stolz, Roswitha; Prasch, Monika; Weber, Michael; Koch, Franziska; Weidinger, Ruth; Ebner, Manuel; Mauser, Wolfram (Journal of Environmental Geography, 2018)
As the Intergovernmental Panel on Climate Change reported in 2013, climate change will have significant impacts on all water sectors. Since water is essential for live, culture, economy and ecosystems, climate change adaptation is crucial. Therefore, a legal and political framework was established by the commissions of the European Union, the United Nations and on national levels. For the Danube River Basin (DRB), the International Commission for the Protection of the Danube River got the mandate to develop an adaptation strategy in 2012 and to update this strategy in 2018. The natural science basis on which the adaptation strategy and its update are based on are two studies, conducted in 2011/2012 and updated and revised in 2017/18. Numerous documents from actual research and development projects and studies dealing with climate change and its impacts on water related issues were analysed in detail and the results summarised. It is agreed that temperature will increase basin-wide. The precipitation trend shows a strong northwest-southeast gradient and significant changes in seasonality. Runoff patterns will change and extreme weather events will intensify. However, the magnitude of the results shows a strong spatial variability due to the heterogeneity of the DRB., It is assessed that these changes will have mostly negative impacts on all water related sectors. Based on the scientific findings an approach for an improved basin-wide strategy on adaptation to climate change is developed. It includes guiding principles and five categories of adaptation measures targeting different objectives.